From Diversity to Confusion? The Challenge of Biodiversity Footprint Quantification - Raphaela Roeder; Sebastian Utz (Business Strategy and the Environment, 2025)
This study documents a significant disagreement between the biodiversity footprints of three major providers. This disagreement mainly stems from fundamental disagreement on the underlying methods and data (measurement), while providers agree to a large part on which firm operations contribute to a loss in biodiversity and how they are aggregated (scope and weight). The disagreement is especially high for large firms with a high biodiversity footprint and firms from the industries of Energy, Consumer Staples, and Basic Materials. A transparent and detailed ESG disclosure can decrease the disagreement. The results highlight the importance of being careful when integrating biodiversity footprint into financial decision-making, regulations, and academic research. The results also underline the need for further standardized and transparent biodiversity disclosure on firm level.
Keywords: 330; biodiversity; biodiversity footprint; disagreement